Choline‐Based Ionic Liquids: Improvement of Antimicrobial Activity. Issue 18 (11th November 2016) - Siopa, Filipa; Figueiredo, Teresa; Frade, Raquel F. M.; Neto, Iris; Meirinhos, Ana; Reis, Catarina P.; Sobral, Rita G.; Afonso, Carlos A. M.; Rijo, Patrícia
Abstract: Antibiotic resistance is a global public health concern. The choline‐based ionic liquids (ILs) have raised particular attention in the design of "greener" ILs and can exert a broad‐spectrum of antimicrobial activity. To improve antimicrobial chemotherapy, we herein tested the antimicrobial activity and toxicity of a wide range of choline‐based ILs. Two series of compounds were synthesized ‐dimethylethanolamine monoquaternary ammonium salts (Series A) and ‐methyl diethanolamine, diethanolamine and triethanolamine monoquaternary ammonium salts (Series B). The antimicrobial screening revealed that compounds N ‐(2‐hydroxyethyl)‐ N, N ‐dimethyl‐1‐tetradecanaminium bromide ( [N 1, 1, 14, 2(OH) ]Br ), N ‐(2‐hydroxyethyl)‐ N, N ‐dimethyl‐1‐hexadecanaminium bromide ( [N 1, 1, 16, 2(OH) ]Br ) and N ‐(2‐hydroxyethyl)‐ N, N ‐dimethyl‐1‐octadecanaminium bromide ( [N 1, 1, 18, 2(OH) ]Br ) are potent antimicrobial agents. The presence of a hydroxyethyl group and as mention previously in the literature, the C14 to C16 linker in a choline compound improves the antimicrobial activity and lowers the cytotoxic properties of this class of compounds. Abstract : The antimicrobial screening to improve antimicrobial chemotherapy of "greener" Ils revealed that [N 1, 1, 14, 2(OH) ]Br is a promising antimicrobial compound, with low cytotoxicity and active against a range of Gram‐negative, Gram‐positive bacteria and also yeasts.